Religious Radicalism , Jihad, And Terrorism - Busman Edyar (Institut Agama Islam Negeri (IAIN) Curup, 2017)
After the terrorist attacked on the twin towers of Word Trade Center, USA, 9 September 2001, the issue of religious radicalism became a serious international concern. Terrorists suspected of carrying certain religious symbols have put religion as the accused party to be responsible. Of course the action did not stand alone. Various variable lighter, should also mentioned why the attitude or behavior of a religious people to be radical and very likely to cause terror. The following study attempts to uncover the background of radicalism in the name of religion appears on the surface. Certainly internal and external factors must be put forward.